POLAR STORAGE METHOD AS ONE QUALITY CONTROL OF RAW MATERIAL FEEDBACK - Prama Wildan Ardiansyah (NAROTAMA UNIVERSITY, Indonesia)
In today's economic development where the business world is growing rapidly, the employers are required to work more efficiently to deal with the tightness of business competition in Indonesia. The continuity of the production process within a company will be influenced by various factors including: Capital, Technology, raw material inventory, finished goods inventory and labor. In addition, the production process must be supported by a good raw material storage process as well.